Prevalence and factors associated with active transportation to school for adolescents - Camargo,Edina Maria de (2020)
ABSTRACT OBJECTIVE: To verify the prevalence and factors associated with active transportation to school (ATS) among Brazilian adolescents attending public schools. METHODS: Crossectional study with a representative sample of 1,984 adolescents (55.9% girls). Sociodemographic variables included were: gender, age, parental schooling, and socioeconomic status. Psychosocial factors included were: social support from parents and friends for physical activity. Walking, cycling, or skateboarding to school were considered models of active transportation. Binary logistic regression models verified sociodemographic and psychosocial factors association with ATS, adopting p < 0.05. RESULTS: The prevalence of active transportation to school was 37.7% (16.2% boys and 21.5% girls). For boys, ATS was associated with: social support from parents in practicing physical activity together as a family (OR = 1.57; 95%CI 1.09–2.25), giving them rides (OR = 1.56; 95%CI 1.04–2.32), and remarking their good performance on it (OR = 1.73; CI95 1.08–2.76); as well as the social support from friends in practicing physical activity together (OR = 2.23; 95%CI 1.35–3.69). For girls, the likelihood of using ATS increased with age (OR = 1.43; 95%CI 1.06–1.92) and having friends who practice physical activity together with them (OR = 1.48, 95%CI 1.04–2.10). CONCLUSION: Age and social support for physical activity were associated with ATS. Parents who practice together, give rides, and remark on physical activities increase the likelihood of adolescent boys using ATS. Social support from friends to physical activity increased the likelihood of both genders using ATS.